Teacher Satisfaction and Its Determinants : Analysis Based on Data from Nigeria and Uganda - Nkengne, Patrick; Pieume, Olivier; Tsimpo, Clarence; Ezeugwu, Gilbert; Wodon, Quentin (Taylor and Francis, 2022)
Teachers who are satisfied with their job are more likely to teach well, which in turn should enable their students to better learn while in school. Sub-Saharan Africa is currently experiencing a learning crisis, with close to nine out of ten children not able to read and understand a simple text at age 10. This affects all types of schools and students, including students in Catholic and other faith-based schools. Improving working conditions and job satisfaction among teachers is part of the answer to this learning crisis. After a brief discussion of data for Nigeria, this article looks at the level of satisfaction of teachers in Uganda, its determinants, and its impact on the quality teaching. Specifically, four questions are asked: What is the level of teacher job satisfaction in Uganda? How does job satisfaction relate to the characteristics of teachers? What is the impact of teachers’ satisfaction on their performance, as it can be measured through various variables of teacher effort? Finally, what are the main factors affecting satisfaction according to teachers? The answers to these questions have implications for policy and practice in faith-based as well as in other schools.